2012
DOI: 10.1007/s00424-012-1169-9
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential canonical channel 1 impacts on mechanosignaling during cell migration

Abstract: Cell migration is crucial for many important physiological and pathophysiological processes ranging from embryogenesis to tumor metastasis. It requires the coordination of mechanical forces generated in different regions of the migrating cell. It has been proposed that stretch-activated, Ca(2+)-permeable channels are involved in mechanosignaling during cell migration. To date, the molecular identity of these channels is only poorly defined. Here, we investigated the contribution of TRPC1 channels to mechanosig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…We determined the intracellular Ca 2+ concentration ([Ca 2+ ] i ) ratiometrically with the fluorescent Ca 2+ indicator fura-2 as described previously [54]. Cells were plated on glass bottom dishes (Willco, Amsterdam, The Netherlands) coated with a basement membrane-like matrix and pretreated in the same way as for migration experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the intracellular Ca 2+ concentration ([Ca 2+ ] i ) ratiometrically with the fluorescent Ca 2+ indicator fura-2 as described previously [54]. Cells were plated on glass bottom dishes (Willco, Amsterdam, The Netherlands) coated with a basement membrane-like matrix and pretreated in the same way as for migration experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that the composition of the mRNA maternal pool of X. tropicalis includes the transcripts of eight non selective cation mechanosen sitive TRP channels. It is essential that the activity of these channels is not only able to depolarize or indi rectly hyperpolarize cell membranes (which itself can regulate cell motility and differentiation) but is also able to regulate the dynamics of cytoplasmic Ca 2+ concentration of [12,14,15], which is an extremely TRPV1 TRPV2 TRPV4 TRPM7 TRPC3 TRPC5 TRPC6 TRPM4 TRPC1 TRPA1 PKD1 PKD2 ODC RT- important secondary messenger. Note that we found the mRNA expression of these channels but not the protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all TRP channels are expressed in the nervous system of vertebrates, and may be involved in the perception of mechanical influ ences, cold, heat, pH or chemical factors. An analysis of the scientific literature revealed TRP ion channels that can be activated in response to a mechanical stim ulus, which, in turn, leads to the regulation of mor phogenesis and differentiation [11][12][13][14][15]. Today, it is known that the following TRP channels are mecha nosensitive: TRPC1, 3, 5, 6, TRPV1, 2, 4, TRPM4, 7, TRPP2 (PKD2) and TRPA1, although, for some of them, this fact is not yet proven conclu sively [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…TRPC1 was found to mediate mechanosensitive currents in neuronal cells (Kerstein et al 2013), migrating Madin-Darby canine kidney (MDCK) cells (Fabian et al 2008(Fabian et al , 2012, mouse brain microvessel endothelial cells (Berrout et al 2012), and primary afferent sensory neurons (Garrison et al 2012). …”
Section: Functionmentioning
confidence: 99%